Effect of RF power and gas ratio on the sidewall of β-Ga2O3 films via inductively coupled plasma etching. (1st January 2023) - Bian, Chunxu; Zhang, Xiaodong; Tang, Wenbo; Zhang, Li; Ma, Yongjian; Chen, Tiwei; Zhou, Xin; Li, Botong; Tang, Jilong; Zeng, Zhongming; Zhang, Baoshun
Abstract: The beveled mesa structure of β -Ga2 O3 has attracted wide attention because it can significantly weaken the peak electric field and increase the breakdown voltage. In this study, β -Ga2 O3 beveled mesa has been modulated via inductively coupled plasma (ICP) etching with the etching precursors of BCl3 and Ar. And the morphology of the sidewall has been investigated by properly adjusting the etching parameters, realizing different beveled angles owing to the different ratios of chemical etching and physical etching. The effect of ICP etching on the sidewall morphology of the β -Ga2 O3 beveled mesa was also studied. This study provides important guidance for the realization of higher-power devices based on β -Ga2 O3 .